(untitled) (CAHIERS MAGELLANES-NS, 2024)
Environmental influences can affect all systems of the body, including blood and mechanisms that ensure its liquid state. At the same time, the influence of physical factors has not been fully evaluated with regard to hemostasis activity. The aim of the work: to trace changes in the activity of hemostasis components in piglets that have undergone an episode of hypothermia due to anthropogenic hydro-impact. A group of 33 2-month-old piglets of the Large White breed was formed, which were exposed to cold water for 2.5 hours due to a technogenic accident. A control group of 35 two-month-old healthy piglets, which did not experience negative environmental influences, was collected from 35 two-month-old healthy piglets kept in the same farm as the group after the negative impact. Activation of platelet aggregation was found in piglets that underwent negative hydro-exposure. Also in these animals there was noted an increase in the functional capabilities of plasma hemostasis with a decrease in the capabilities of fibrinolysis. This situation aggravated the phenomena of microcirculation in the organs of animals. The coming slowdown of hemorheology in microvessels inhibited metabolism and weakened their organism as a whole. In piglets that experienced an episode of hypothermia, a functional biologically disadvantageous strengthening of hemostasis work is formed, which can impede the processes of microcirculation and, consequently, the phenomena of anabolism in their tissues. In this regard, it seems important to evaluate in future studies the effect of various optimizing influences on the activity of individual components of hemostasis in piglets that have undergone negative hydroexposure.